Evolving in isolation: Genetic tests reject recent connections of Amazonian savannas with the central Cerrado - Resende-Moreira, Luciana C.; Knowles, L. Lacey; Thomaz, Andréa T.; Prado, Joyce R.; Souto, Andrea P.; Lemos-Filho, José P.; Lovato, Maria Bernadete (Journal of biogeography, 2019)
Aim The effects of past climatic shifts remain enigmatic for the Amazon region, especially for islands of savanna within the tropical forest known as “Amazonian savannas” (AS). These disjunct savanna areas share many plant and animal species with the Cerrado biome in central Brazil (the CC), fuelling debate over historical connections. We evaluate hypothesized corridors between the CC and the AS, and specifically investigate whether a history of isolation versus recent connections is supported by genetic tests. Location Cerrado and Amazon biomes. Taxon Two woody plant species: Byrsonima coccolobifolia and B. crassifolia (Malpighiaceae). Methods Analyses of genomic data (SNPs from more than 4,500 loci) in 28 populations, as well as chloroplast DNA (cpDNA), were used to test for parallel geographic structuring between the CC and AS—an expected structure if putative corridors provided regional connections between different areas of the CC and AS, and divergence times between the CC and AS were estimated using a composite‐likelihood method based on the site frequency spectrum. Results Genomic data, in contrast with cpDNA, generally show strong, concordant genetic structure between the CC and AS in both species, rather than regional grouping of CC with AS populations. In addition, divergence between the CC and AS predates the Last Glacial Maximum. Main conclusions Our results suggest the AS have remained relatively isolated from the CC even though the strong structure of genomic variation is not shared by cpDNA. We note that past evidence of putative corridors between the CC and AS based solely on cpDNA should be interpreted cautiously since the lack of structure may reflect limited genetic resolution rather than gene flow. As such, the uniqueness of AS may be more pronounced than previously thought, highlighting the importance of protecting these highly threatened areas.